Disruption of intestinal barrier and endotoxemia after traumatic brain injury: Implications for post‐traumatic epilepsy. (23rd April 2021) - Mazarati, Andrey; Medel‐Matus, Jesus‐Servando; Shin, Don; Jacobs, Jonathan P.; Sankar, Raman
Abstract: Objective: Traumatic brain injury (TBI) may lead to the disruption of the intestinal barrier (IB), and to the escape of products of commensal gut bacteria, including lipopolysaccharide (LPS), into the bloodstream. We examined whether lateral fluid percussion injury (LFPI) and post‐traumatic epilepsy (PTE) are associated with the increased intestinal permeability and endotoxemia, and whether these events in turn are associated with PTE. Methods: LFPI was delivered to adult male Sprague‐Dawley rats. Before, 1 week, and 7 months after LFPI, the IB permeability was examined by measuring plasma concentration of fluorescein isothiocyanate–labeled dextran (FD4) upon its enteral administration. Plasma LPS concentration was measured in the same animals, using enzyme‐linked immunosorbent assay. PTE was examined 7 months after LFPI, with use of video‐EEG (electroencephalography) monitoring. Results: One week after LFPI, the IB disruption was detected in 14 of 17 and endotoxemia – in 10 of 17 rats, with a strong positive correlation between FD4 and LPS levels, and between plasma levels of each of the analytes and the severity of neuromotor deficit. Seven months after LFPI, IB disruption was detected in 13 of 15 and endotoxemia in 8 of 15 rats, with a strong positive correlation between plasma levels of the two analytes. Five of 15 LFPI rats developed PTE. Plasma levels of both FD4 and LPS were significantly higher in animals with PTE than among the animals without PTE. The analysis of seven rats, which were examined repeatedly at 1 week and at 7 months, confirmed that late IB disruption and endotoxemia were not due to lingering of impairments occurring shortly after LFPI. Significance: LFPI leads to early and remote disruption of IB and a secondary endotoxemia. Early and late perturbations may occur in different subjects. Early changes reflect the severity of acute post‐traumatic motor dysfunction, whereas late changes are associated with PTE.